Inhibitory Effects of Palmatine on P2X7 Receptor Expression in Trigeminal Ganglion and Facial Pain in Trigeminal Neuralgia Rats - Yin, Cancan; Shen, Wenhao; Zhang, Mingming; Wen, Lequan; Huang, Ruoyu; Sun, Mengyun; Gao, Yun; Xiong, Wei (Frontiers in Cellular Neuroscience, 2021)
Trigeminal Neuralgia (TN) refers to recurrent severe paroxysmal pain in the distribution area of the trigeminal nerve, which seriously affects the quality of life of patients. This research applied the chronic constriction injury of the infraorbital nerve (CCI—ION) approach to induce an animal model of TN in rats. The mechanical pain threshold of each group of rats was determined postoperatively; the expression of P2X7 receptor in trigeminal ganglion (TG) was assessed by qRT-PCR, immunofluorescence and Western blot; and the changes of the proinflammatory cytokines IL-1β and TNF-α in serum of rats were detected by ELISA. The results showed that the administration of palmatine in the TN rats could reduce the mechanical pain threshold, significantly decrease the expression of P2X7 receptor in TG, and lower the serum concentrations of IL-1β and TNF-α, compared to the sham group. In addition, the phosphorylation level of p38 in TG of TN rats was significantly decreased after treatment with palmatine. Likewise, inhibition of P2X7 expression by shRNA treatment could effectively counteract the adversary changes of pain sensitivity, IL-1β and TNF-α production, and p38 phosphorylation in TN rats. Our data suggest that palmatine may alleviate mechanical facial pain in TN rats possibly by reducing the expression of P2X7 receptor in TG of TN rats, which may be attributable to inhibiting p38 phosphorylation and reducing the release of IL-1β and TNF-α.